Velcro Ties in Early Postoperative Pediatric Tracheostomy Care: A Systematic Review and Meta‐analysis. (13th October 2020) - Chang, Brent A.; Gurberg, Joshua; Ware, Erin; Luu, Kimberly
Abstract : Objective: To systematically review the literature to determine the difference in complications between standard twill and Velcro ties following pediatric tracheostomy. Data Sources: MEDLINE, Embase, the Cochrane Database of Systematic Reviews, the Cochrane Central Register of Controlled Trials, Web of Science, and CINAHL Plus were searched up to August 2020. Review Methods: Two authors independently screened articles for eligibility. Retrospective and prospective studies were included as long as there was a direct comparison between twill and Velcro ties. Quantitative and qualitative analysis was performed. The main outcomes were skin‐related complications and accidental decannulation. Results: Three studies were included in the final analysis: 1 randomized prospective trial and 2 retrospective studies. There were 238 patients total (137 twill, 101 Velcro). Combined analysis showed skin‐related complications in 23% of the Velcro group and 44% of the twill group. Meta‐analysis for skin‐related complications showed no significant difference when comparing Velcro with standard twill ties (risk ratio, 0.53 [95% CI, 0.24‐1.17]; P =. 12, n = 238 participants from 3 studies, I 2 = 66%). Accidental decannulation rates were overall low and comparable between groups (1.0% of twill, 1.4% of Velcro). Conclusion: Based on limited data, skin‐related complications were not statistically different between Velcro and twill ties. Accidental decannulation is rare with Velcro and standard twill ties, and both are viable options following pediatric tracheostomy.